Yes [videorecording (DVD)] - Realbuto, Tim; Realbuto, Tim; Realbuto, Tim; Gould, Nolan; Hogan, Siobhan Fallon; Nuñez, Oscar; Realbuto, Tim (Safier Entertainment, 2025)
Tells the story of washed up child star Patrick Nolan who decides to mentor 17-year-old Jeremiah Rosenhaft.